Avaliação da qualidade de pisos comerciais confeccionados com madeiras de Bowdichia nitida Benth (Spr.), Dipterxy odorata (aubl.) Willd, Mimosa scabrella Benth e Tabebuia impetiginosa - Oliveira, Mônica Bezerra de (2015)
Wooden floors are used in residential, commercial and industrial environments, being a highly demanded and appreciated material. Given the demand for commonly used species, new species are commercially employed in the market. This conjuncture increases the range of products made available to consumers. One of the ways to guarantee quality and obtain information for improving the use of wooden floors is to conduct trials that simulate its use in service. These trials simulate the friction existent on the contact zones of the floor, the pressure caused by punctual loads and the drag and fall of objects. However, the lack of regularization of reference class values is the largest difficulty for establishing the quality of wooden floors. The objective of this work was to establish value classes for the quality of wooden floors by means of service simulation trials. For this, we used commercial floors made of woods from Bowdichia nitida Benth (Spr.) – Sucupira, Dipterxy odorata (aubl.) Willd – Cumaru, Mimosa scabrella Benth – Amendola and Tabebuia impetiginosa – Ipe. It was possible to establish three distinct quality classes, high, intermediate and low. The ipe and cumaru floors were the most resistant, while the sucupira floors presented intermediate resistance and the amendola floors presented lower resistance and a higher number of depressions.